Studi Keanekaragaman Jenis Burung di Jalur Tracking Pemo, Taman Nasional Kelimutu, Kabupaten Ende, Provinsi Nusa Tenggara Timur - Graciano Vivio de Araujo; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2025)
In Indonesia there are around 1737 species of birds (Birdlife International 2023). However, the status of birds in Indonesia is also endangered and this status continues to increase. Based on Birdlife International (2023), there are 162 species of birds that are threatened globally with a percentage of 10% of the total bird species in Indonesia. Kelimutu National Park offers a variety of habitats that support the life of various bird species. One of the areas of interest to research is the Tracking Pemo trail, which is known for its natural beauty and diversity of ecosystems. This study aims to measure the diversity of bird species in the Kelimutu National Park Pemo Tracking route and determine the conservation status based on the regulation of the Minister of Environment and Forestry (Permen LHK No.P, 106/2018) and the IUCN (International Union For Conservation Of Nature) Threatened status. This study was conducted from October to November 2023 using the Mackinnon species list method. The results of the study show that the richness and diversity of bird species found in the Pemo tracking path is that there are 35 species of birds from 23 families that have high diversity, and there are also 10 types of protected birds in the Pemo tracking trail area. There is 1 type of endemic bird, namely the Flores Kancilan (Pachycephala nudigula) which has 15 kinds of cuara or chirping. Of the 35 types of birds found, there are species of Perkici Flores birds whose status is almost threatened/NT and 34 other species have LC (Low Risk) status.